A parallel framework for unstructured grid solvers - Burgess, D; Crumpton, P; Giles, M (Unspecified, 1995)
The aim of this work is the parallel solution of large two and three dimensional CFD problems using unstructured grids. A general framework has been formulated to enable both parallel and sequential execution of a single source FORTRAN code. This is achieved via the straightforward insertion of OPlus (Oxford Parallel Library for Unstructured Solvers) subroutine calls . Hence, the user's code can be developed, debugged and maintained on a sequential machine and executed in parallel when required. The generality is achieved through the specification by the programmer of certain key aspects of the data structure used in the computation. However, the programmer need not be aware of the underlying details of the parallel execution of the application and therefore the development of the parallel application is greatly simplified.